TRAINING ON MAKING CATFISH OIL JELLY CANDY TO INCREASE TODDLER WEIGHT AND PREVENT MALNUTRITION FOR THE PKK GROUP IN RINDU HATI VILLAGE - Versita, Riana; Kurnia Dewiani (Journal of Community Service, 2026)
The issue of malnutrition among toddlers in Bengkulu Province, particularly in Rindu Hati Village, Central Bengkulu Regency, has become a major concern with a prevalence of 2.4%. This condition requires innovative solutions utilizing local resources to improve the nutritional status of toddlers. This study aims to train the PKK group in Rindu Hati Village to utilize catfish, an abundant local resource, by processing it into jelly candies enriched with fish oil. The product is designed to enhance toddlers' weight with an appealing taste, minimizing the fishy odor, and providing additional economic value. The method employed is Participatory Rural Appraisal (PRA), engaging the community in the production process. The expected outcomes include increasing the PKK members' understanding of the benefits of fish oil and equipping them with the skills to produce jelly candies as a solution for preventing malnutrition. This training is anticipated to not only improve the nutritional status of toddlers but also empower the local community economically through innovations in catfish-based food products.